2009
DOI: 10.1590/s1806-37132009001200011
|View full text |Cite
|
Sign up to set email alerts
|

O papel do estresse oxidativo na DPOC: conceitos atuais e perspectivas

Abstract: centers such as the city of São Paulo ranges from 6% to over 15%, depending on the diagnostic criteria adopted.(4) The fifth leading cause of death worldwide, COPD will have reached, according to recent estimates, the third position by 2030.(3) The increase in the mortality rate for COPD contrasts with the marked reduction in the mortality rate for diseases such as cancer, IntroductionWorldwide, COPD is a health problem with severe economic and social repercussions; at the personal level, COPD constitutes a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 52 publications
(101 reference statements)
0
15
0
5
Order By: Relevance
“…Many studies suggested that COPD was related to respiratory, diaphragmatic, and skeletal muscle dysfunction [27, 31–33]. Mitochondrial electron transport-related molecules (NAD/NADH/ADP) are also in relation with redox reactions and oxidative stress, which are known to be the key factors in COPD [33, 34]. In addition, regulation of interleukin expression, involved in inflammation, is also a symptom of COPD [3537].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies suggested that COPD was related to respiratory, diaphragmatic, and skeletal muscle dysfunction [27, 31–33]. Mitochondrial electron transport-related molecules (NAD/NADH/ADP) are also in relation with redox reactions and oxidative stress, which are known to be the key factors in COPD [33, 34]. In addition, regulation of interleukin expression, involved in inflammation, is also a symptom of COPD [3537].…”
Section: Discussionmentioning
confidence: 99%
“…The most important processes causing lung damage are oxidative stress produced by the high concentrations of free radicals in tobacco smoke and cytokine release due to inflammatory response to irritant particles such as tobacco smoke in the airways (21). Smoking and exacerbations of COPD result in decreased antioxidant capacity in plasma that can be explained by the increased radical oxygen species release from peripheral blood neutrophils (22, 23) or decreased levels of major plasma antioxidants such as vitamin C or E in smokers (18, 24).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress and inflammation were also associated with increased total respiratory resistance in our hyperoxia animals, and studies have shown other clinical complications following oxidative injury as well. 25,3335 …”
Section: Discussionmentioning
confidence: 99%